Sade : The Invention Of The Libertine Body - Henaff, Marcel (Book collections on Project MUSE., 1999)
Decried as a misogynist and pornographer, imprisoned for debauchery and for his writings, there is scarcely a cultural figure as flamboyant and controversial as the Marquis de Sade, the father of the new libertine body. But this is not the only way to see Sade. In this long-awaited English translation, Henaff says that Sade should be discussed less for the sensual heat of his writing and more for the larger poetic and economic model his work represents.